STUDI ANALISIS BIAYA DISTRIBUSI DAN EFEKTIVITAS RUTE PADA SISTEM LOGISTIK DISTRIBUSI PT. SEMEN PADANG - Rida Yanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The efficiency of logistics distribution systems plays a critical role in ensuring the timely and cost-effective delivery of goods. This study aims to conduct a comprehensive analysis of distribution costs and evaluate route effectiveness within the logistics distribution process. With the increasing complexity of supply chain networks, companies are challenged to optimize transportation routes while minimizing operational expenses. The research focuses on identifying key cost components, such as fuel consumption, vehicle maintenance, labor, and time-related costs, and correlates these with route planning strategies. A case study approach was utilized, incorporating real-world data from a distribution company operating in urban and semi-urban areas. Quantitative methods, including cost analysis, route mapping using Geographic Information Systems (GIS), and vehicle routing problem (VRP) modeling, were employed to evaluate multiple distribution scenarios. The study also incorporates qualitative insights from logistics managers and drivers to understand on-ground constraints and decision-making processes. Findings reveal that route optimization, through the use of technology and data-driven planning, can significantly reduce total distribution costs—up to 25% in some cases—while improving delivery reliability and customer satisfaction. Inefficiencies in current routing practices, such as suboptimal path selection and poor load management, were identified as major contributors to cost overruns. Recommendations include the adoption of dynamic routing algorithms, integration of real-time traffic data, and strategic scheduling based on demand patterns. This study contributes to the body of knowledge in logistics and supply chain management by highlighting the interplay between cost control and routing efficiency, offering practical solutions for enhancing distribution system performance.